Effects of the KiVa Anti-bullying Program on Adolescents' Depression, Anxiety, and Perception of Peers - Williford A; Boulton A; Noland B; Little TD; Karna A; Salmivalli C (SPRINGER/PLENUM PUBLISHERS, 2022)
The present study investigated the effects of the KiVa antibullying program on students' anxiety, depression, and perception of peers in Grades 4-6. Furthermore, it was investigated whether reductions in peer-reported victimization predicted changes in these outcome variables. The study participants included 7,741 students from 78 schools who were randomly assigned to either intervention or control condition, and the program effects were tested with structural equation modeling. A cross-lagged panel model suggested that the KiVa program is effective for reducing students' internalizing problems and improving their peer-group perceptions. Finally, changes in anxiety, depression, and positive peer perceptions were found to be predicted by reductions in victimization. Implications of the findings and future directions for research are discussed.